Penggunaan Citra sebagai Penyuluhan Masyarakat yang Berada di Rawan Terjadi Bencana Tanah Longsor - Ridho’i, Ahmad; Sidiq, Nujhad; Sarya, Gede; Andriawan, Aris Heri (Jurnal Pengabdian Masyarakat Bhinneka, 2025)
Landslides are a serious threat in various regions of Indonesia, causing material losses and casualties. Communities residing in landslide-prone areas often have a low level of understanding and awareness regarding disaster risks and their mitigation. Therefore, this community service aims to implement and evaluate the effectiveness of using imagery as an innovative and easily understandable outreach medium for communities in landslide-prone areas. Conventional, verbally-oriented outreach methods are often less effective in conveying technical information to the general public, especially given varying literacy levels. This community service adopts a descriptive qualitative approach with case studies in several villages in Ponorogo, East Java, identified as landslide-prone areas. Data was collected through participant observation, in-depth interviews with community representatives and village officials, and Focus Group Discussions (FGDs). The imagery used in this service includes aerial photographs, disaster-prone maps, and visual illustrations of landslide mechanisms, early warning signs, and relevant evacuation and mitigation steps. These images were then integrated into interactive outreach materials and presented in engaging formats, such as infographics, posters, and visual presentations.